Inventory of leafhoppers in irrigated rice in Tamil Nadu - Atee, Feby; Chitra, N; Venugopal, Sheela; Kumaraperumal , R (ORYZA-An International Journal of Rice, 2023)
Leafhoppers diversity was studied in irrigated rice ecosystems of Cauvery Delta Zone, High Rainfall Zone and Western Zone. Leafhopper assemblage comprised 14 species of Cicadellidae and among them Maiestas dorsalis (Motschulsky) was found to be the most abundant species (35.02%), followed by Cofana spectra (Distant) (23.15%). The order of species diversity in the observed districts were Western Zone (13 species) > High Rainfall Zone (8 species) > Cauvery Delta Zone (4 species). Shannon Weiner Index revealed a higher diversity in High Rainfall Zone and Western Zone (H’= 1.77 > 1.76). Margalef’s Index of species richness was observed highest in Western Zone (a = 1.93). Pielou’s Evenness Index was found to be almost similar for Western Zone (0.30) and Cauvery Delta Zone (0.29) while High Rainfall Zone exhibited highest evenness (0.37). Jaccard index of similarity of 50% (highest) was observed between Western Zone and Kanyakumari, Cauvery Delta Zone and High Rainfall Zone. Berger-Parker Index of dominance (D) revealed M. dorsalis to be the most dominant in Western Zone (0.25) and Cauvery Delta Zone (0.66) while High Rainfall Zone showed a high dominance of Nephotettix nigropictus (Stål) (0.27). Among the leafhoppers studied Balclutha incisa (Matsumura), Cicadulina bipunctata (Melichar), Empoascanara maculifrons (Motschulsky), Exitianus sp., Thomsonia porrecta (Walker) were recorded for the first time in rice ecosystem of Tamil Nadu. The present study will be a baseline information on the diversity of leafhoppers in irrigated rice of Tamil Nadu and will complement the data collected in the future to gain a holistic understanding on the leafhopper diversity of Tamil Nadu.